2012
DOI: 10.1007/s10880-012-9318-z
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth, Posttraumatic Stress Symptoms and Mental Health Among Coronary Heart Disease Survivors

Abstract: The present study aimed to estimate posttraumatic stress symptoms (PTSS) and posttraumatic growth (PTG) among heart disease survivors and examine whether PTG moderates the association between PTSS and mental health. Data from 82 myocardial infarction and acute coronary artery bypass graft survivors (aged 46-82) was obtained at admission to a cardiac rehabilitation unit. Mental status was assessed by the PTSD Inventory, Posttraumatic Growth Inventory (PTGI), Mental Health Inventory and Health Related Quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 37 publications
7
60
0
3
Order By: Relevance
“…These results suggest that severe pain might hinder post-traumatic growth. However, some studies on posttraumatic growth in other populations, such as individuals with cancer, coronary heart disease and deployed soldiers, demonstrated that post-traumatic growth is related to higher levels of trauma and suffering which is sufficient to induce life changes [44][45][46]. Since there are few studies on the relationship between pain and post-traumatic growth, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that severe pain might hinder post-traumatic growth. However, some studies on posttraumatic growth in other populations, such as individuals with cancer, coronary heart disease and deployed soldiers, demonstrated that post-traumatic growth is related to higher levels of trauma and suffering which is sufficient to induce life changes [44][45][46]. Since there are few studies on the relationship between pain and post-traumatic growth, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Those who felt fear of dying had significantly more anxiety and avoidance-focused coping strategies (data not shown in the tables). Previous studies reported a prevalence of PTSD between 9.4 percent and 27 percent after ACS (Bedi and Arora, 2007;Bluvstein et al, 2013;Edmondson et al, 2011;Ginzburg, 2006;Guler et al, 2009;Shemesh et al, 2006;Spindler and Pedersen, 2005;Von Kanel et al, 2011;Whitehead et al, 2006;Wikman et al, 2008). According to the DSM-IV definition, PTSD has to occur after a traumatic event or life-threatening illness (Gander and Von Kanel, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic growth, the perception of positive benefits arising from trauma, may moderate the association between PTSD symptoms and mental health outcomes following cardiac surgery. 28 …”
Section: Assuaging Worrymentioning
confidence: 99%